30 Rock - Season 7 Episode 1-13 - Scardino, Don; MacCarthy-Miller, Beth; Riggi, John; Reniers, Peter; Fey, Tina; Baldwin, Alec; Morgan, Tracy (Universal Pictures, 2016)
As Jack schemes to take control of kabletown or sink the whole company trying, Liz strives to balance her uncharacteristically blissful personal life with the constant chaos of her career. Even with Kenneth Parcell (Jack McBrayer), lifelong NBC devotee, temporary janitor, and immortal creature not of this earth, around to tend to TGS’ loveable misfit stars, Tracy Jordan (Tracy Morgan) and Jenna Maroney (Jane Krakowski), 30 Rock mayhem ensues with a season full of network tanking, election meddling, upward spiralling, funeral weddings, Florida, reverse health scares, sacrificial bunions, symphonic "Sanford and Son" arrangements, last lunches and boat modeling. [www.amazon.co.uk]
Keywords: DVD-Video